Parental Support in Smartphone-Based Reading Instruction: A Qualitative Case Study of Elementary Literacy Development - Sekar Ayu Pramadhita; Fitri Puji Rahmawati (Journal of Educational Sciences, 2026)
The increasing integration of smartphones into elementary education presents both opportunities and challenges for literacy development. While digital tools can enhance engagement, their effectiveness depends largely on structured implementation and adult mediation. This study aims to explore the role of parental support in smartphone-based reading instruction and its influence on students’ reading fluency, comprehension, and motivation. A qualitative case study was conducted in an elementary school involving three fifth-grade students, three parents, and three teachers who participated directly in the smartphone-assisted reading program. Data were collected through interviews, classroom observations, and document analysis, and were analyzed thematically. The findings indicate that smartphone-assisted reading, when guided by teachers and supported by parents, enhances students’ engagement and contributes to gradual improvement in reading fluency. However, challenges such as distraction, screen fatigue, technical limitations, and inconsistent parental supervision were also identified. The study concludes that smartphones function effectively as complementary literacy tools when embedded within structured instructional design and collaborative home–school practices. Sustainable implementation requires balanced screen management, pedagogical planning, and strengthened parental involvement to ensure meaningful literacy development.